2022
DOI: 10.3389/fenvs.2022.939296
|View full text |Cite
|
Sign up to set email alerts
|

Drift macroalgae positively influence seagrass-associated nekton communities of the northern Gulf of Mexico

Abstract: Drift macroalgae, often found in clumps or mats adjacent to or within seagrass beds, can provide additional food resources and habitat complexity, leading to increased animal abundance, but large concentrations can also inhibit faunal movements, smother benthic communities, and contribute to hypoxia, reducing nekton abundance. Despite its ubiquity, few studies have quantified drift macroalgal prevalence over large spatial scales or its effects on seagrass-associated nekton, hindering our understanding of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The degradation of these clumps on top of these small filter-feeding invertebrates may cause an increase in nutrients and hypoxia, together with a physical barrier for capturing food particles from the water column, causing a decline in their population [32]. Indeed, some authors have detected an increase in deposit feeders together with declines in filter feeders and photosynthetic organisms in areas with large clumps of drifted algae [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The degradation of these clumps on top of these small filter-feeding invertebrates may cause an increase in nutrients and hypoxia, together with a physical barrier for capturing food particles from the water column, causing a decline in their population [32]. Indeed, some authors have detected an increase in deposit feeders together with declines in filter feeders and photosynthetic organisms in areas with large clumps of drifted algae [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…When not in excess, macroalgae coexist with seagrass meadows and provide support to community and ecosystem secondary productivity. For instance, drift algae in the Northern Gulf of Mexico have been found to positively influence seagrass-related nekton recruitment and biomass (Correia and Smee, 2022;Correia et al, 2022b). However, the recent IPCC Special Report on the Ocean and Cryosphere in Changing Climate (Bindoff et al, 2019) reported a widespread increase in coastal stress levels, noting that since 1980, shifts in seaweeds and harmful algal blooms, that often interact negatively with seagrass meadows, have also increased in range and frequency.…”
Section: Introductionmentioning
confidence: 99%